Feminine Characterization of The God - Ibrahim Bor (Şırnak Üniversitesi İlahiyat Fakültesi Dergisi)

(untitled)
This study investigates how monotheistic religions depict God with masculine or feminine attributes, considering historical context. The issue arises from questioning the portrayal of a masculine God within these religions, influenced by a patriarchal socio-cultural backdrop. Instances mainly from Christianity and lesser from Judaism and Islam, the study analyzes the characteristics of religious theological language used in the depiction of God. In this context, we explore the linguistic challenge encountered by religious traditions when employing anthropomorphic language. Since the core issue revolves around expressing and labeling the divine, the paper initiates with a conceptual examination of God’s characterization as either masculine or feminine. In this analysis, tracing back historically, archaeological and anthropological evidence indicates that language used to describe God was initially predominantly feminine. Feminist perspectives contend that over time, particularly within monotheistic religions, this language has become masculine and that this historical shift has been a major factor in the social and cultural exclusion of women. Against this claim, the study aims to substantiate the claim that despite the effective historical dominance of the theological masculine language, the feminine divine image persists in both theistic and non-theistic traditions. Both the Holy Scriptures and early theological writings occasionally employ feminine language when discussing God, although less frequently than masculine language. Within this context, anthropomorphic depictions of God in the Holy Books of monotheistic religions—where God is perceived as an immaterial being—are interpreted metaphorically, analogically, or symbolically. In particular, the mystical traditions of these religions have emphasized feminine qualities more intensely in their depiction of the divine. They portray God not only as a father or male figure but also with feminine attributes, such as a mother, lover, or friend. These traditions contend that qualities like divine beauty and mercy find their fullest expression in women and the feminine manifestation of existence. Notably, the Nag Hammadi tradition, rooted in Jewish mysticism, highlights the feminine dimensions of the divine, emphasizing love and compassion. Medieval Christian mystics such as Meister Eckhart and Julian of Norwich also emphasized the feminine dimension of God in their experience of the divine. Similarly, within Islamic Sufism, influenced by the Our’an’s balance and harmony of tanzih(exoneratin God from human attributes) and tashbih (drawing similitude) the Ibn Arabi tradition, emphasizing the feminine portrayal of the divine. They recognized the divine presence within the feminine elements of creation. Additionally, a lesser-known figure, Molla al-Jaziri, dealt extensively with the theme of woman as a divine mirror. This study aimed aligns with the feminist theological approach, advocating for the reinterpretation of theological and religious language in order to liberate it from the dominance of a patriarchal language and reveal its feminine aspect. Additionally, study also suggests further research by examining specific time periods, approaches and individual scholars’ perspectives.